Predicting European Enlargement Impacts: A Framework of Inter-regional General Equilibrium - d'Artis Kancs (Economics and Econometrics Research Institute (EERI), 2001)
Although the Computable General Equilibrium (CGE) model is not a new tool for analysing policy impacts, it has not gained a wide popularity in regional applications such as rural economies yet. This study demonstrates how a regional CGE model can be applied for analysing regional impacts of changing global economic conditions as well as for assessing inter-regional and inter-sectoral implications of policy changes with even limited computational resources and lacking a full range of regional economic data required by a formal CGE analysis. In the empirical analysis we have found that rural economies in the Central and Eastern European (CEE) accession countries may expect the largest welfare gains from integration into the European Union (EU) if the EU Structural Fund and CAP support measures are implemented immediately but markets are opened gradually to foreign competition.
Keywords: D51; R12; R13; R23; 330; CGE; EU; regional economies; economic integration